SLANG WORDS IN BIRDS OF PREY MOVIE - Christiana, Elisabeth May; Fadillah, Eka; Rachmawaty, Endar (Universitas Widya Kartika Surabaya, 2021)
[Slang Words in Birds of Prey Movie] This study aimed to analyze slang words appeared in Birds of Prey Movie. This study intended to find the types of slang words used by the main characters in Birds of Prey movie and used by the main characters in the movie. This study applied a descriptive qualitative approach. It is categorized as sociolinguistic because this study focuses on social context of social factors in utterances. The data were collected from the utterances of the main characters, Harley, Cass, Roman, Zsasz, Canary, Renee, and Huntress. The researchers utilized Chapman’s theory to identify the types of slang words and Holmes’s theory to analyze the social context as well as the meaning of the slang words. The result encompasses the type of slang words: primary and secondary slang words. Recommendation and implication are discussed further.